Reigniting Empowerment of Tribal Women in Suriname through Engagement in Transformative Technology -Phase II - Delice, Curt Delelis (2025)
With the collaboration of the Inter-American Institute for Cooperation on Agriculture (IICA), Inter-American Development Bank (IDB), IDB Lab (Multilateral Investment Fund) and Wi! Uma Fu Sranan